2018
DOI: 10.1021/jacs.8b05298
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Atom Vacancy Formation at Polyoxovanadate Clusters: Homogeneous Models for Reducible Metal Oxides

Abstract: We report the first example of oxygen-atom vacancy formation at the surface of a polyoxometalate, highlighting the ability of a polyoxovanadate-alkoxide cluster, [VO(OCH)], to function as a homogeneous model for reducible metal oxides. The removal of an oxide ion from [VO(OCH)] results in the formation of a reactive vanadium(III) cation within the multimetallic framework. Generation of [VO(OCH)] is confirmed by H NMR, infrared and electronic absorption spectroscopies, as well as electrospray ionization mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
136
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(161 citation statements)
references
References 52 publications
24
136
1
Order By: Relevance
“…Given the significance of the proposed reduced species in these molecular transformations, extensive efforts have focused on the isolation and characterization of oxygen-deficient POMs. However, to date, examples of well-defined polyoxoanions containing a coordinatively unsaturated, reduced ion, generated via reduction of the parent metal oxide cluster, remain scarce 29,3437…”
Section: Introductionmentioning
confidence: 99%
“…Given the significance of the proposed reduced species in these molecular transformations, extensive efforts have focused on the isolation and characterization of oxygen-deficient POMs. However, to date, examples of well-defined polyoxoanions containing a coordinatively unsaturated, reduced ion, generated via reduction of the parent metal oxide cluster, remain scarce 29,3437…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Avila et al [ 70 ] performed extensive density functional theory (DFT) calculation and concluded the highest possible oxidation state of all 10 V atoms in decavandate clusters as 5+. The work of Petel et al [ 60 ] provides enough evidence in support of natural presence of OVs in neutral and stable POM clusters. Proper external electric stimuli (in case of RRAMs, it is the bias voltage applied between top and bottom contacts) can further multiply the number of OVs within the POM matrix facilitating fast and reversible redox reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[ 67 ] Furthermore, Petel et al also carried out extensive investigation of a vanadium‐based POM to study presence of OV sites within the molecular cluster. [ 60 ] They too argued that such vacancy sites are formed naturally at the surface of the POM clusters as a result of removal of neutral oxygen atoms from it. The structure then gets reduced through delocalization of electronic charge density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations